A comparison of uniaxial and borehole jack tests at Fort Providence Ice Crossing, 1995 - Masterson, D. M.; Graham, W. P.; Childs, G. R.; Jones, S. J. (1996)
A field test program was conducted on the ice bridge crossing near Fort Providence, N. W. T. during March, 1995. Cores of ice were extracted and tested on a portable test frame in uniaxial compression at a strain-rate of 2 x 10-3s-1. The ice temperature varied from -6 to -15º C over the course of the tests. In the core holes, in-situ strength tests were performed using a borehole jack. Tests were conducted in both the natural ice and the sprayed ice, to obtain a correlation between unaxial compression strengths and the strengths obtained by the borehole jack. Based on our results and previous practice, the factor of safety for the ice crossing against flexural failure ws about 4. NRC publication: Yes